Effect of intensive care unit diary on quality of life of intensive care unit survivors and their relatives: A systematic review and meta‐analysis - Donghui Hu; Xiaoli Ji; Yaxin Li; YueNing Liang; Jia Chen (Wiley, 2023)
Abstract Aim To evaluate the current literature on the effect of ICU diaries on the quality of life of ICU survivors and their relatives. Design Systematic review and meta‐analysis. Methods We searched the online databases Web of Science, PubMed, Embase, The Cochrane Library, CNKI and WanFang from inception to April 2021. Cochrane Risk of Bias Assessment Tool and Newcastle-Ottawa Scale (NOS) were used to assess the methodological quality. Results Seven studies were identified. ICU diaries improved the QoL of ICU survivors (SMD 0.79, 95% CI 0.24-1.34), and a small study described no benefit of diaries in improving the QoL of relatives. Conclusion This meta‐analysis revealed the use of ICU diaries to improve the QoL in survivors, but the ICU diaries do not have a beneficial effect on the QoL in relatives. The evidence summarized in our study is limited and biased, and more research should be carried out to verify it.